Cantwell, Theresa Squires. Colour wedding anniversary photograph of three men and three women from Theresa Squires Cantwell's personal photograph collection. - Barrett, Terra
50th wedding anniversary of William and Madeline Squires. Madeline Squires was from Topsail and was born Halley. Left to right: Alex Haley, Jack Murphy, William Squires, Madeline Squires, Theresa Druken, and Eileen Druken.